2021
DOI: 10.48550/arxiv.2103.08308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning for Massive Industrial Internet of Things

Abstract: Industrial Internet of Things (IIoT) revolutionizes the future manufacturing facilities by integrating the Internet of Things technologies into industrial settings. With the deployment of massive IIoT devices, it is difficult for the wireless network to support the ubiquitous connections with diverse quality-of-service (QoS) requirements. Although machine learning is regarded as a powerful data-driven tool to optimize wireless network, how to apply machine learning to deal with the massive IIoT problems with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…More importantly, it has been shown that even a single malicious participant can significantly alter the trained model [16]. Therefore, it is imperative to make FL robust to Byzantine failures, in particular for security-critical IIoT applications such as automated guided vehicles and robot motion control [17].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, it has been shown that even a single malicious participant can significantly alter the trained model [16]. Therefore, it is imperative to make FL robust to Byzantine failures, in particular for security-critical IIoT applications such as automated guided vehicles and robot motion control [17].…”
Section: Introductionmentioning
confidence: 99%